2018
DOI: 10.1080/00498254.2018.1426133
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2A6 and other human P450 enzymes in the oxidation of flavone and flavanone

Abstract: 1. We previously reported that flavone and flavanone interact spectrally with cytochrome P450 (P450 or CYP) 2A6 and 2A13 and other human P450s and inhibit catalytic activities of these P450 enzymes. In this study, we studied abilities of CYP1A1, 1A2, 1B1, 2A6, 2A13, 2C9 and 3A4 to oxidize flavone and flavanone. 2. Human P450s oxidized flavone to 6- and 5-hydroxylated flavones, seven uncharacterized mono-hydroxylated flavones, and five di-hydroxylated flavones. CYP2A6 was most active in forming 6-hydroxy- and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 63 publications
(91 reference statements)
1
39
0
Order By: Relevance
“…Flavonoids generally have low bioavailability due to interactions with digestive enzymes and intestinal microorganisms [ 18 ]. Flavanones were metabolized to flavone by CYP2A6 and CYP2A13 in the liver [ 19 ] and mainly excreted in urine within 4–8 h [ 20 ]. In this study, the compounds were intravenously administered to avoid intestinal interactions; therefore, the toxicity would be observed in nonmetabolized forms of TH011 and TH002 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids generally have low bioavailability due to interactions with digestive enzymes and intestinal microorganisms [ 18 ]. Flavanones were metabolized to flavone by CYP2A6 and CYP2A13 in the liver [ 19 ] and mainly excreted in urine within 4–8 h [ 20 ]. In this study, the compounds were intravenously administered to avoid intestinal interactions; therefore, the toxicity would be observed in nonmetabolized forms of TH011 and TH002 .…”
Section: Resultsmentioning
confidence: 99%
“…in the rat (10 mg, single dose) and 47 min. in human (20 mg, iv drip) [ 32 ], mainly by CYP2A6 and CYP2A13 metabolism [ 19 ] and renal clearance. Therefore, further in vivo efficacy should include the multiple doses of administration in order to maintain the therapeutic level during viremia or febrile phase.…”
Section: Discussionmentioning
confidence: 99%
“…Biological activities of flavonoids vary with the number and substitution positions of hydroxyl and/or methoxy groups [54]. Kakimoto et al [55] showed that CYP2A6 and other human P450s play important roles in the metabolism of flavone and flavanones. According to Bojic et al [56].…”
Section: Bioavailability and Drug Interactionsmentioning
confidence: 99%
“…difficulty of their extraction from plant sources or the necessity for complicated procedures to obtain them synthetically. Several papers have reported flavonoid hydroxylations catalyzed by P450s from mammals [54], plants [55], bacteria [56] or fungi [57]. To the best of our knowledge, production of 3-hydroxyflavanone with flavanone as substrate was only reported recently, in a whole-cell system expressing CYP110E1 from Nostoc sp.…”
Section: Biosynthesis Of Differently Hydroxylated Flavonoids Is Of Himentioning
confidence: 99%